The comparison of gasless and traditional robot-assisted transvaginal natural orifice transluminal endoscopic surgery in hysterectomy - Mei, Youwen; He, Li; Zhang, Qiang; Chen, Ying; Zheng, Jiafeng; Xiao, Xinyu; Lin, Yonghong (Frontiers in Medicine, 2023)
Study objective To describe the surgical technique and compare the operative outcomes of gasless and traditional robot-assisted transvaginal natural orifice transluminal endoscopic surgery (GR-vNOTES vs. TR-vNOTES) in hysterectomy. Methods The patients undergoing hysterectomy via GR-vNOTES or TR-vNOTES between February 2020 and January 2022 in our hospital were included. Clinical data regarding patient demographics, operative time, blood loss, complications, and postoperative hospital stays were collected and analyzed. Results Five cases underwent hysterectomy via GR-vNOTES, and nine cases via TR-vNOTES. The baseline demographics and operative outcomes were not significantly different in GR-vNOTES and TR-vNOTES groups. There was no conversion to multiport robotic laparoscopy, conventional laparoscopy or laparotomy. No complications were seen in both groups, except two cases had fever postoperatively in the TR-vNOTES group. For those with early stage cervical/endometrial cancer, no recurrence or metastasis was observed in the follow-up of six months. Conclusion Both GR-vNOTES and TR-vNOTES were feasible and safe for hysterectomy. GR-vNOTES was a promising alternative to TR-vNOTES in hysterectomy.